Evolution of electronic waste toxicity: Trends in innovation and regulation. (April 2016) - Chen, Mengjun; Ogunseitan, Oladele A.; Wang, Jianbo; Chen, Haiyan; Wang, Bin; Chen, Shu
Abstract: Rapid innovation in printed circuit board, and the uncertainties surrounding quantification of the human and environmental health impacts of e-waste disposal have made it difficult to confirm the influence of evolving e-waste management strategies and regulatory policies on materials. To assess these influences, we analyzed hazardous chemicals in a market-representative set of Waste printed circuit boards (WPCBs, 1996–2010). We used standard leaching tests to characterize hazard potential and USEtox® to project impacts on human health and ecosystem. The results demonstrate that command-and-control regulations have had minimal impacts on WPCBs composition and toxicity risks; whereas technological innovation may have been influenced more by resource conservation, including a declining trend in the use of precious metals such as gold. WPCBs remain classified as hazardous under U.S. and California laws because of excessive toxic metals. Lead poses the most significant risk for cancers; zinc for non-cancer diseases; copper had the largest potential impact on ecosystem quality. Among organics, acenaphthylene, the largest risk for cancers; naphthalene for non-cancer diseases; pyrene has the highest potential for ecotoxicological impacts. These findings support the need for stronger enforcement of international policies and technology innovation to implement the strategy of design-for-the-environment and to encourage recovery, recycling, and reuse of WPCBs. Graphical abstract: Highlights: We demonstrated WPCBs remain potentially dangerous to human health and environment. Regulations and technologies have influenced the use of materials in WPCBs. We revealed the new risk factors not sufficiently addressed by existing regulation.